TRANSINTERNALIZATION OF ISLAMIC EDUCATION CULTURE - Rachmat Panca Putera; Noor Fadhzana (Jurnal Ilmiah AZZIQRI: Kajian Keislaman dan Kependidikan, 2022)
Thoughts on the development of Islamic education to encourage critical analytical thinking,creative and normative in the face of various practices and current issues in the field ofeducation weeks to be studied and analyzed from its foundational dimensions so as not to losethe spirit or the spirit of Islam and / fragility philosophical foundation, as well as the face of thetrend. Emphasis on the importance of students to live by the values of goodness, spiritualityand morality as neglected. In fact the opposite is happening. Nowadays, many educationalinstitutions have been transformed into industrial business, which has a pragmatic vision andmission. Education geared to deliver pragmatic individuals who work to achieve materialsuccess and social professions that will prosper themselves, companies and countries. Insecular Western culture, a person's high education does not correspond to the goodness andhappiness of the individual concerned. The impact of the hegemony of Western education onMuslims is that many Muslims have a high education, but in real life, they have not becomegood and happy Muslims. There is still a gap between the high degree of education achievedand the low morals and morals of Muslim life. This is due to the pragmatic vision and missionof education. Actually, Islam has a more comprehensive and integrative goal than the seculareducation system which solely produces students who have a pragmatic paradigm. they havenot become good and happy Muslims. There is still a gap between the high degree of educationachieved and the low morals and morals of Muslim life. This is due to the pragmatic vision andmission of education. Actually, Islam has a more comprehensive and integrative goal than thesecular education system which solely produces students who have a pragmatic paradigm. theyhave not become good and happy Muslims. There is still a gap between the high degree ofeducation achieved and the low morals and morals of Muslim life. This is due to the pragmaticvision and mission of education. Actually, Islam has a more comprehensive and integrativegoal than the secular education system which solely produces students who have a pragmaticparadigm.